IMPLEMENTASI METODE OUTDOOR STADY DALAM PEMBELAJARAN IPA UNTUK MENINGKATKAN PEMAHAMAN PELESTARIAN ALAM - Trimansyah Trimansyah (FASHLUNA, 2022)
This paper discusses the implementation of science learning using the outdoor stadium method as an effort to increase or develop students' understanding of the importance of preserving nature. To instill this understanding in students, it is necessary to be creative from a teacher in carrying out varied learning so that the teaching and learning process can run more effectively and efficiently, moreover how to make learning fun for students. Of course all of that requires various methods and strategies used in learning, with regard to learning this science, using the Outdoor Stady method is one of the right methods as a means of achieving goals in learning, namely learning is done outside the classroom with the aim that students can understand clearly. directly about nature or the surrounding environment, learning outside the classroom will be more influential in developing the abilities and skills of students and will be more effective for students in developing all their potential and intelligence.